1998
DOI: 10.1002/(sici)1097-0177(199806)212:2<171::aid-aja3>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency assessment of the gene trap approach

Abstract: The trapping of genes in murine embryonic stem (ES) cells offers three features in one experimental approach: 1) analysis of the expression patterns of unknown genes by using a simple staining method, 2) rapid cloning of unknown genes, and 3) generation of mutant mouse lines. We performed a gene trap screen aimed at the discovery of new genes regulating embryonic development. We have processed 209 gene trap events for expression patterns in chimeric murine embryos. Randomly tested, β‐galactosidase‐positive ES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…When we analyzed Mena protein levels in our Mena GT/GT mice, we found that specifically in the brain, but not in other organs, the gene trap was “leaky” [27,28], resulting in a low amount of endogenous full length protein (data not shown but compare Mena protein levels in the Mena GT/GT VASP −/− organs, Figure 3A, dKO lanes). We speculated that the residual Mena expression in the brain of Mena GT/GT mice may overcome the embryonic lethal phenotype of Mena/VASP double-deficient mice and crossed the Mena GT/GT animals with our VASP −/− mice [16].…”
Section: Resultsmentioning
confidence: 99%
“…When we analyzed Mena protein levels in our Mena GT/GT mice, we found that specifically in the brain, but not in other organs, the gene trap was “leaky” [27,28], resulting in a low amount of endogenous full length protein (data not shown but compare Mena protein levels in the Mena GT/GT VASP −/− organs, Figure 3A, dKO lanes). We speculated that the residual Mena expression in the brain of Mena GT/GT mice may overcome the embryonic lethal phenotype of Mena/VASP double-deficient mice and crossed the Mena GT/GT animals with our VASP −/− mice [16].…”
Section: Resultsmentioning
confidence: 99%
“…A C-terminal tag containing the V5 epitope 66 was introduced into the Moz locus by homologous recombination in ES cells followed by germline chimera production, as described previously. 67 Mice containing the tagged Moz allele were bred to homozygosity to show that the presence of the tag did not impede MOZ function. Although Moz −/− null mice die at or before birth, Moz V5/V5 mice were viable and fertile.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…The configuration of bgeo used in our reporters has been extensively reported in gene trap screens, generating very similar percentages of bgal negative clones (40-70% depending on the selection conditions; Bonaldo et al, 1998;Skarnes et al, 1995;Tate et al, 1998;Tzouanacou et al, 2003;Voss et al, 1998;Wilson et al, 1995). This is consistent with our findings, suggesting that there is no adverse effect of the GFP fusion upon bgeo.…”
mentioning
confidence: 86%